2020
DOI: 10.1038/s41392-020-0158-2
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study of methylprednisolone therapy in severe patients with COVID-19 pneumonia

Abstract: , in Wuhan, China. There are over 1,800,000 confirmed cases worldwide. 1 The pathological process of severe COVID-19 pneumonia is an inflammation reaction characterized by the destruction of the deep airway and alveolar. 2 It is currently considered that lung injury is not only associated with the direct virus-induced damage, but also the immune responses triggered by COVID-19 that lead to the activation of immune cells to release a large number of pro-and anti-inflammatory cytokines. Histologic examination ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
193
1
11

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(223 citation statements)
references
References 5 publications
10
193
1
11
Order By: Relevance
“…[33] Fernandez-Cruz et al reported lower mortality in patients with COVID-19 pneumonia complicated with ARDS and/or a hyperin ammatory syndrome treated with corticosteroids (HR 0.36, 95% CI 0.14 to 0.93, p=0.04). [46] In the other four studies, no signi cant difference in mortality rates between steroid and non-steroid groups, [36,40,48] or even an increased risk in the group that received corticosteroids was demonstrated. [50] However, Lu et al did note that every increase of 10 mg in hydrocortisone equivalent dosage was associated with a 4% elevation of the mortality risk (HR 1.04, 95% CI 1.01-1.07).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…[33] Fernandez-Cruz et al reported lower mortality in patients with COVID-19 pneumonia complicated with ARDS and/or a hyperin ammatory syndrome treated with corticosteroids (HR 0.36, 95% CI 0.14 to 0.93, p=0.04). [46] In the other four studies, no signi cant difference in mortality rates between steroid and non-steroid groups, [36,40,48] or even an increased risk in the group that received corticosteroids was demonstrated. [50] However, Lu et al did note that every increase of 10 mg in hydrocortisone equivalent dosage was associated with a 4% elevation of the mortality risk (HR 1.04, 95% CI 1.01-1.07).…”
Section: Resultsmentioning
confidence: 88%
“…[42,43] In the remaining eight studies, the risk of corticosteroid use was quanti ed, and these were included to calculate the pooled estimate. [23,33,36,37,40,46,48,50] The overall pooled estimate (observational studies and the RCT) showed a favorable outcome in the corticosteroid group (relative risks RR 0.55, 95% CI 0.27-0.83, random effects) ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations